2014
DOI: 10.1016/j.stemcr.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Debra-Mediated Ci Degradation Controls Tissue Homeostasis in Drosophila Adult Midgut

Abstract: SummaryAdult tissue homeostasis is maintained by resident stem cells and their progeny. However, the underlying mechanisms that control tissue homeostasis are not fully understood. Here, we demonstrate that Debra-mediated Ci degradation is important for intestinal stem cell (ISC) proliferation in Drosophila adult midgut. Debra inhibition leads to increased ISC activity and tissue homeostasis loss, phenocopying defects observed in aging flies. These defects can be suppressed by depleting Ci, suggesting that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Considering that SUMO substrates are highly enriched for transcription factors (Hendriks et al, 2014), a likely candidate is Ci, a transcription factor of the Hh pathway (Hui and Angers, 2011;Li et al, 2014;Motzny and Holmgren, 1995). Ci can interact directly with Lwr (Fig.…”
Section: The Sumo Pathway Directly Modifies CImentioning
confidence: 99%
“…Considering that SUMO substrates are highly enriched for transcription factors (Hendriks et al, 2014), a likely candidate is Ci, a transcription factor of the Hh pathway (Hui and Angers, 2011;Li et al, 2014;Motzny and Holmgren, 1995). Ci can interact directly with Lwr (Fig.…”
Section: The Sumo Pathway Directly Modifies CImentioning
confidence: 99%
“…Secreted Hedgehog proteins constitute a major family of signaling molecules that guide development, cell proliferation and stem cell behavior in Drosophila and in mammals (Hui and Angers, 2011;Briscoe and Therond, 2013;Zhang and Kalderon, 2001;Peng et al, 2013;Petrova et al, 2013;Li et al, 2014). Accordingly, genetic alterations affecting Hedgehog (Hh) signaling are responsible for a variety of developmental defects and cancers, prompting the development of promising therapeutic drugs (Ng and Curran, 2011;Metcalfe and de Sauvage, 2011;Amakye et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both EGFR signaling (Biteau and Jasper, 2011;Buchon et al, 2010;Jiang et al, 2011;Xu et al, 2011) and Hh signaling (Han et al, 2015;Li et al, 2014;Tian et al, 2015) have been shown to promote ISC division during normal midgut homeostasis and regeneration. In addition to the JAK-STAT pathway, we also confirmed the activation of EGFR and Hh signaling in the Sulf1 mutant midgut as follows: (1) upregulation of the vn-lacZ reporter (Yarnitzky et al, 1997) in visceral muscles (Fig.…”
Section: P1mentioning
confidence: 99%
“…It has been shown that ISC division and differentiation are regulated by several signaling pathways, including Janus kinase and signal transducer and activator of transcription (JAK-STAT), epidermal growth factor receptor (EGFR), Hedgehog (Hh), bone morphogenetic protein (BMP) and Wingless (Wg) signaling (Ayyaz et al, 2015;Beebe et al, 2010;Biteau and Jasper, 2011;Buchon et al, 2009aBuchon et al, ,b, 2010Cordero et al, 2007Cordero et al, , 2012Cronin et al, 2009;Guo et al, 2013;Jiang et al, 2009Jiang et al, , 2011Lee et al, 2009;Li et al, 2014Li et al, , 2013bLin et al, 2008Lin et al, , 2010Liu et al, 2010;Osman et al, 2013;Tian and Jiang, 2014;Tian et al, 2015;Xu et al, 2011;Zhou et al, 2013Zhou et al, , 2015. In response to tissue damage, the ligands of these pathways are transcriptionally upregulated in cells surrounding ISCs, and activate signal transduction in ISCs to promote their division.…”
Section: Introductionmentioning
confidence: 99%